Particle swarm optimisation classical and quantum perspectives - Sun, Jun, 1971- (Chapman & Hall/CRC numerical analysis and scientific computing., 2012)
"This volume provides a detailed description of the state of the art of particle swarm optimization (PSO) and quantum-behaved particle swarm optimization (QPSO) algorithms. The authors present the motivation, principles, and theoretical analysis of the algorithms. They discuss advanced topics such as the behavior of individual particles, global convergence, time complexity, and rate of convergence. The authors also present various examples and applications to show the applicability of QPSO algorithms. In addition, the book includes the source code of the algorithm"--